ANALISIS MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK PEMBANGUNGAN JEMBATAN BERDASARKAN ISO 31000:2018 - Heru Prasetya Nugroho; Edy Purwanto (JOURNAL SAINS STUDENT RESEARCH, 2024)
The Yogyakarta-Bawen toll road project package 1 section 1 includes Sleman-Bayurejo which requires building a bridge on STA 0+625 using the bore pile method. The purpose of the study is to examine the application of risk management in the STA 0+625 bridge construction project on the Yogya-Bawen toll road project package 1 section 1 based on ISO 31000:2018. The method used used was a survey questionnaire in data collection to obtain risk level values and determine risk response. The results were then validated through interview media. From the results of the interview, it can also be known the risk control actions taken by stakeholders to overcome risks. The results of the study showed 39 risk variables identified in the implementation of bridge construction projects, 14 categories of high risk, 24 categories of medium risk and 1 category of low risk. In the results of risk response mapping based on probability and consequence values, there are 7 categories of risk reduction, 31 categories of risk transfer and 1 category of risk avoidance. It is known that the match between the interview results and the calculation of risk response is 15%.